Air dehumidification by cooled adsorption in silica gel grains. Part II: Theoretical analysis of the prototype testing results. (5th January 2017) - Pistocchini, Lorenzo; Garone, Silvia; Motta, Mario
Highlights: Theoretical analysis of fixed bed adsorption dehumidification. Development of semi-empirical formulas for COP and dehumidification rate calculation. Assessment of energy performance dependence on operating conditions. Comparison of different control strategies. Abstract: The study concerns the theoretical investigation of the performances of a fixed-bed adsorption dehumidifier, based on the results of a comprehensive testing campaign. By analyzing the batch operation of the system and fitting the experimental data related to different operating conditions, two semi-empirical formulas have been developed to accurately predict the dehumidification rate and the thermal COP of the prototype. Such formulas allow implementing different control strategies of the dehumidifier, prioritizing the saving of either electricity or thermal power. The approach we used in developing the equations may be usefully applied to other similar batch operated systems.